HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra (1982)
A photo of Band members in the Orange Lodge. Florence Worthman, Edmund Worthman, Joseph Legge, Eddie Chislett, Stan Reid, unknown and unknown.